2020
DOI: 10.1111/jfpp.14424
|View full text |Cite
|
Sign up to set email alerts
|

The degradation of forchlorfenuron in the model kiwifruit juice by ultrasonic treatment

Abstract: Forchlorfenuron (CPPU), as a plant growth regulator, is widely applied to promote fruits and vegetables yield. The degradation of CPPU in model kiwifruit juice by sonication was investigated in the present study. Results showed that bath sonication was effective in eliminating CPPU in model kiwifruit juice, and the ultrasonic power, time and temperature significantly influenced the degradation of phorate (p < .05).The maximum degradations were achieved 72.01% after the ultrasonic treatment at 600 W, 45°C for 4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 26 publications
0
3
0
Order By: Relevance
“…Similarly, Słowik-Borowiec and Szpyrka [23] reported an ultrasonic washing caused a significant reduction of 84 % in fluopyram than boiling at 100 °C (72.1 %) and tap water washing (56.2 %) in apple samples. Sonication is effective for agrochemical degradation in pakchoi leaves [21] and fruit juice [24] , [25] .…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, Słowik-Borowiec and Szpyrka [23] reported an ultrasonic washing caused a significant reduction of 84 % in fluopyram than boiling at 100 °C (72.1 %) and tap water washing (56.2 %) in apple samples. Sonication is effective for agrochemical degradation in pakchoi leaves [21] and fruit juice [24] , [25] .…”
Section: Introductionmentioning
confidence: 99%
“…However CPPU treatment tends to reduce the quality of fruits and vegetables, and may lead to the presence of CPPU residue in fruits and vegetables when they enter the market [3]. In addition, excessive intake of CPPU can lead to protein metabolism disorders, mild emphysema, and emaciation, which is serious and potentially harmful to human beings [4,5]. To protect public health, many countries strictly limit the maximum residue limit (MRL) of CPPU in fruits and vegetables to not exceeding 50 μg/kg [6].…”
Section: Introductionmentioning
confidence: 99%
“…A chronic toxicity study on CPPU revealed its potentially negative effects on the ovaries [ 9 ]. In addition, long-term exposure to CPPU can induce acute and chronic intoxication and irritation to the eyes and skin [ 10 ]. Hence, to protect public health, many countries have issued a maximum residue limit (MRL) for CPPU.…”
Section: Introductionmentioning
confidence: 99%